Internet-based problem shopping behavior: online shopping addiction - Bal, Fatih; Okkay, İpek (Journal of Dependence, 2022)
With interactive technologies, consumers have become able to shop twenty-four hours a day, seven days a week, three hundred and sixty-five days a year. Today, online shopping has become an increasingly attractive alternative to shopping in real environments for most people. The freedom to act independently of time and place, the ease of accessing the desired product with one click, the possibility of price comparison, and the possibility of accessing all kinds of products with lower prices, provided by online shopping, and similar features not only make life easier but also lead to problematic online shopping behaviors. Shopping is a phenomenon that the consumer society imposes with mass media for the continuation of the system. Although consumption becomes excessive, it causes material and moral harm to the individual and those around him; However, shopping addiction is a disease in consumer societies; it is not perceived as a disease. As a product of popular culture, advertisements offer people desirable life patterns. People need to be accepted sociologically, and to be liked psychologically lead them to comply with these messages and consume them even if they do not need them. When this consumption becomes uncontrollable, the individual suffers both materially and morally. Over time, shopping addicts harm their families, relationships, friendships, and careers and get into financial trouble. In this context, compulsive shopping disorders can be seen as dangerous as any other mental disorder. This study aims to give detailed information on the concept of online shopping addiction in line with its relationship with compulsive and addictive consumption and purchasing behaviors in both marketing communication and psychology literature. The research examined the studies in the literature by using the “literature review” method. As a result, although there is still debate about whether compulsive buying disorder is a valid psychological diagnosis, it has been observed that some people are addicted to shopping. This addiction is triggered by marketing communication messages, and they need help for their addiction.